2008
DOI: 10.1161/hypertensionaha.108.114991
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Calcium and Vitamin D Supplementation on Blood Pressure

Abstract: Abstract-Experimental and epidemiological studies suggest that calcium and vitamin D supplements may lower blood pressure. We examined the effect of calcium plus vitamin D supplementation on blood pressure and the incidence of hypertension in postmenopausal women. The Women's Health Initiative Calcium/Vitamin D Trial randomly assigned 36 282 postmenopausal women to receive 1000 mg of elemental calcium plus 400 IU of vitamin D3 daily or placebo in a double-blind fashion. Change in blood pressure and the inciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
131
2
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 222 publications
(140 citation statements)
references
References 36 publications
(34 reference statements)
5
131
2
2
Order By: Relevance
“…These findings are consistent with several short-term (Pan et al, 1993;Major et al, 2007) and long-term trials (Orwoll and Oviatt, 1990;Margolis et al, 2008) that reported that combined calcium-vitamin D supplementation did not lower blood pressure. To the best of our knowledge, our study is the longest trial to have assessed the blood pressure responses to additional calcium-vitamin D 3 , using food (milk) as a carrier.…”
Section: Discussionsupporting
confidence: 90%
“…These findings are consistent with several short-term (Pan et al, 1993;Major et al, 2007) and long-term trials (Orwoll and Oviatt, 1990;Margolis et al, 2008) that reported that combined calcium-vitamin D supplementation did not lower blood pressure. To the best of our knowledge, our study is the longest trial to have assessed the blood pressure responses to additional calcium-vitamin D 3 , using food (milk) as a carrier.…”
Section: Discussionsupporting
confidence: 90%
“…In the Women's Health Initiative, an RCT including 36,282 postmenopausal women, vitamin D 3 plus calcium supplementation did not reduce blood pressure, nor the risk of developing hypertension over seven years of follow-up; however in this trial supplementation consisted only of 400 IU/day and adherence to supplementation was only around 60% [26]. A recent meta-analysis of 8…”
Section: Effects Of Vitamin D On the Cardiac Systemmentioning
confidence: 66%
“…19 The recently published Women's Health Initiative trial, which included 36 282 nonpregnant postmenopausal women randomised to supplementation with 1000 mg calcium and 10 lg (400 IU) vitamin D or placebo, showed no difference in systolic and diastolic BP or the development of hypertension over a median of 7 years of follow up. 20 The role of vitamin D in prevention and treatment of hypertensive disorders requires further evaluation.…”
Section: Discussionmentioning
confidence: 99%